THE POTENTIAL OF TRICHODERMA BIOCONTROL AGENTS FOR INCREASING THE PRODUCTION OF SOYBEAN PLANTS RESISTANT TO SOYBEAN MOSAIC VIRUS - Annisa’ Indah Setyawati; Herfandi Lamdo; Indah Hafidhotun Nisa (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
SMV infection at early growth stages can reduce crop productivity by 25.48% to 93.84%. Viral infections may reduce plant growth due to disruptions in physiological processes and photosynthetic output, hormonal imbalances, and decreased nutrient uptake, ultimately preventing the plant from growing optimally. The research was conducted at the Experimental Field and Basic Science Laboratory of the Faculty of Agricultural Technology, Satu Nusa Lampung University, as well as the Analysis Laboratory of Politeknik Negeri Lampung, from May to August 2025. The method used in this research was an experimental method. The study employed a Randomized Complete Block Design (RCBD) with the following treatments: T0 = Control, T1 = 10 ml Trichoderma solution, T2 = 20 ml Trichoderma solution, T3 = 30 ml Trichoderma solution, T4 = 40 ml Trichoderma solution,T5 = 50 ml Trichoderma solution per plant (with a spore concentration of 1 ml T. asperellum = 46.5 × 10² spores). Result Based on the study of the potential of Trichoderma asperellum in enhancing the resistance of soybean plants infected with SMV, it can be concluded that the 50 ml T. asperellum treatment showed the best results, with an incubation period of 18 days after inoculation (DAI), disease severity of 14%, and a plant resistance rating categorized as resistant to SMV. The highest yield increase was also recorded in the 50 ml Trichoderma treatment (T5), reaching 77.45%.